Quality of life domains affected in women with breast cancer - Sabrina Nunes Garcia; Michele Jacowski; Gisele Cordeiro Castro; Carila Galdino; Paulo Ricardo Bittencourt Guimarães; Luciana Puchalski Kalinke
OBJECTIVE: This study aimed to investigate the quality of life of women suffering from breast cancer undergoing chemotherapy in public and private health care systems. METHOD: It is an observational, prospective study with 64 women suffering from breast cancer. Data was collected with two instruments: Quality of Life Questionnaire C30 and Breast Cancer Module BR23. By applying Mann Whitney and Friedman's statistical tests, p values < 0.05 were considered statistically significant. RESULTS: The significant results in public health care systems were: physical functions, pain symptom, body image, systemic effects and outlook for the future. In private health care systems, the results were sexual, social functions and body image. Women's quality of life was harmed by chemotherapy in both institutions. CONCLUSION: The quality of life of women has been harmed as a result of the chemotherapy treatment in both institutions, but in different domains, indicating the type of nursing care that should be provided according to the characteristics of each group.